A large-area light-rechargeable zinc ion soft-pack battery and its preparation method and application
By using a femtosecond laser system and expanded polytetrafluoroethylene film sealing technology in light-rechargeable zinc-ion soft-pack batteries, the optical window and bonding area are optimized, which solves the problems of battery sealing and light energy utilization when the battery is enlarged in size, and achieves efficient light energy collection and stable battery performance.
Patent Information
- Application Number
- CN202510999105.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-21
- Publication Date
- 2025-09-12
- Estimated Expiration
- 2045-07-21
AI Technical Summary
Existing photorechargeable zinc-ion batteries have problems such as easy electrolyte leakage, decreased mass-to-capacity of active materials, zinc dendrites piercing the diaphragm causing short circuits, and low light energy collection efficiency when the battery size is enlarged. In addition, traditional processes are difficult to solve the problem of coordinated design of optical windows, electrodes, and packaging, resulting in decreased battery performance.
A femtosecond laser system is used to process optical windows and hole arrays on the aluminum-plastic film, combined with expanded polytetrafluoroethylene film sealing, a modular structure is designed, the optical window size and bonding area are optimized, and acrylic adhesives and UV curing technology are used to ensure battery sealing and light energy utilization.
The light energy collection efficiency and packaging reliability of the battery are improved, the battery capacity is significantly increased, the cycle performance is excellent, it is suitable for large-scale production and has low cost.
Smart Images

Figure CN120511406B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy, and in particular to a large-area light-rechargeable zinc ion soft-pack battery and a preparation method and application thereof. Background Art
[0002] In recent years, photorechargeable zinc-ion batteries (Zn-ion batteries) have shown significant potential in distributed energy systems due to their ability to directly utilize solar energy to increase capacity and self-charge. However, existing technologies still face the following key bottlenecks in practical applications, severely hindering their scalable development and performance improvement: First, traditional photorechargeable batteries mostly use a CR-2032 button cell structure, which suffers from low battery capacity, small window area, and low light energy collection efficiency. While common flexible packaging solutions increase the light-transmitting area, they often suffer from electrolyte leakage and a significant decrease in the specific capacity of the active material mass after scaling up. Furthermore, when scaling up the battery size, conventional processes can easily cause localized growth of zinc dendrites due to uneven contact between the current collector and the active material, which can pierce the separator, causing short circuits and shortening the battery's cycling performance. Despite attempts to improve this, the challenge of optical window-electrode-encapsulation coordinated design remains unresolved, resulting in a significant performance degradation after scaling up the battery capacity. Therefore, there is an urgent need to develop a photorechargeable Zn-ion soft-pack battery system that balances high light transmission efficiency, structural stability, photoelectrochemical performance, and process scalability. Summary of the Invention
[0003] The present invention aims to overcome the shortcomings of the prior art and provides a large-area light-rechargeable zinc ion soft-pack battery, a preparation method thereof, and applications thereof. By designing the structure of the light-rechargeable zinc ion soft-pack battery and optimizing the size of the optical window, the present invention not only maintains the good sealing performance of the battery, but also increases the capacity of the light-rechargeable zinc ion soft-pack battery and improves the utilization rate of light energy.
[0004] To achieve the above purpose, the technical solution designed by the present invention is as follows:
[0005] The present invention provides a method for preparing a large-area light-rechargeable zinc ion soft-pack battery, comprising the following steps:
[0006] (1) Fold the aluminum-plastic film in half along the center of the edge, and use a femtosecond laser system to process an optical window in the center of one side of the aluminum-plastic film;
[0007] (2) Define the bonding area around the optical window and use a femtosecond laser system to process the hole array in the bonding area;
[0008] (3) Cleaning the aluminum-plastic film and expanded polytetrafluoroethylene film after processing in step (2);
[0009] (4) bonding the expanded polytetrafluoroethylene film to the bonding area of the aluminum-plastic film using an acrylic adhesive, and performing UV curing to obtain an aluminum-plastic film bonded with the expanded polytetrafluoroethylene film;
[0010] (5) Cleaning and drying the titanium mesh, rolling the photo-positive electrode material onto the titanium mesh, and obtaining a photo-rechargeable positive electrode sheet after drying;
[0011] (6) From bottom to top, the zinc metal negative electrode sheet, GF / D glass fiber separator and photorechargeable positive electrode sheet are encapsulated in an aluminum-plastic film bonded with expanded polytetrafluoroethylene film. After the zinc ion battery is assembled, the electrolyte is added and the edges are hot-pressed to obtain a large-area photorechargeable zinc ion soft-pack battery.
[0012] Furthermore, in step (1), the area of the optical window is 14-64% of the top surface area of the large-area light-rechargeable zinc-ion soft-pack battery;
[0013] The femtosecond laser system has a wavelength of 750-850 nm, a pulse width of 45-55 fs, and a repetition frequency of 0.5-1.5 kHz.
[0014] Furthermore, the area of the optical window is 14-36% of the top surface area of the large-area light-rechargeable zinc-ion soft-pack battery.
[0015] Furthermore, in step (2), the width of the bonding area is 0.2 to 0.8 cm;
[0016] The hole array is composed of multiple hole array units, each of which is a square with a side length of 0.2~0.8. Each hole array unit has four small squares of the same size. There are circular holes distributed at the center point of each small square and the center point of each hole array unit. The aperture of the circular holes is 1~1.5μm.
[0017] Furthermore, in step (3), the thickness of the expanded polytetrafluoroethylene film is 10-50 μm;
[0018] The cleaning is performed using a plasma cleaning machine. The plasma of the plasma cleaning machine is argon gas with a flow rate of 50-70 sccm, a radio frequency power of 180-300 W, and a cleaning time of 240-360 seconds.
[0019] Furthermore, in step (4), the amount of the acrylic adhesive is 5-10 μL / cm 2 The UV curing time is 10~40 seconds, and the UV curing power is 2~10 watts.
[0020] Furthermore, in step (5), the cleaning is performed by ultrasonic cleaning with anhydrous ethanol for 25 to 30 minutes, and the loading amount of the photo-positive electrode material on the photo-rechargeable positive electrode sheet is 8 to 15 mg / cm 2 ;
[0021] The preparation steps of the photocathode material are as follows:
[0022] V6O 13 The nanosheets and the conductive agent are mixed, and after grinding, a binder is added, and the photocathode material is obtained by wetting and stirring.
[0023] Furthermore, the conductive agent is any one of acetylene black, Super P and carbon nanotubes, and the adhesive is any one of PTFE emulsion and PVDF emulsion;
[0024] Conductive agent and V6O 13 The mass ratio of nanosheets is 1:2~4, and the mass volume ratio of the conductive agent and the adhesive is 1:0.55~1 mg / μl;
[0025] V6O 13 The preparation steps of the nanosheets are as follows:
[0026] Dissolve vanadium pentoxide and oxalic acid dihydrate in water, heat and stir, and then perform hydrothermal reaction. After the reaction is completed, cool and filter to obtain precipitate, wash and dry to obtain V6O 13 nanosheets;
[0027] The mass ratio of vanadium pentoxide to oxalic acid dihydrate is 1.8-3:2.7-4.5, the heating and stirring temperature is 60-90° C., the heating and stirring time is 45-75 minutes, the hydrothermal reaction temperature is 160-200° C., and the hydrothermal reaction time is 160-200 minutes.
[0028] Furthermore, in step (6), the zinc metal negative electrode sheet is obtained by ultrasonically cleaning and drying zinc foil, and the thickness of the zinc foil is 30-200 μm;
[0029] The electrolyte is any one of zinc trifluoromethanesulfonate electrolyte, zinc sulfate electrolyte and zinc chloride electrolyte, and the concentration of the electrolyte is 0.8-3 mol / L;
[0030] The hot pressing edge sealing is performed twice, the hot pressing temperature is 110-200° C., the hot pressing pressure is 0.2-0.8 MPa, the first hot pressing time is 3-6 seconds, and the large-area light-rechargeable zinc-ion soft-pack battery is turned over before the second hot pressing is performed, and the second hot pressing time is 1-3 seconds.
[0031] The present invention also provides a large-area light-rechargeable zinc ion soft-pack battery prepared by the preparation method.
[0032] The present invention also provides an application of the large-area light-rechargeable zinc ion soft-pack battery in the field of energy storage.
[0033] Principle of the present invention:
[0034] 1. The present invention uses expanded polytetrafluoroethylene film (ePTFE film) to seal the optical window. Its ultra-thin state (10-50μm thickness) has a light transmittance of up to 95-98%, close to the transparency of glass. At the same time, it has excellent chemical corrosion resistance (resistant to strong acids, strong bases and organic solvents) and extreme temperature adaptability (long-term stability from -240°C to 260°C). The microporous design of the ePTFE film gives the material excellent breathability, waterproofing and filtering functions, and combined with the super-hydrophobic surface (water contact angle >110°), it achieves a self-cleaning effect.
[0035] 2. The present invention designs a hole array in the bonding area so that the bonding area is covered with micron-sized hole units, which is beneficial for the adhesive to fully contact the material surface and enhance the bonding strength. The core principle is the mechanical interlocking mechanism. After the adhesive is injected, the micron-sized holes form small anchor points at the bonding interface, which enhances the physical bonding force of the interface and increases the difficulty of interface separation. In addition, the design of the hole array unit effectively increases the bonding area and improves the stress distribution of the bonding interface, avoiding overall failure due to local failure of the bonding interface. According to experimental tests, in order to ensure both the light energy utilization rate and the sealing strength of the soft-pack battery, the optical window area is strictly controlled to be 14~64% of the top surface area of the soft-pack battery, the bonding width is 0.2~0.8cm, and an acrylic adhesive is used in an amount of 5~10μL / cm 2 .
[0036] Beneficial effects of the present invention:
[0037] 1. This invention successfully overcomes the technical bottleneck of conventional light-rechargeable zinc-ion pouch cells through innovative optical window design and optimized light-storage synergy. The use of a centrally positioned, area-adjustable optical window, combined with a highly transparent sealing interface, significantly improves light energy collection efficiency while ensuring battery packaging reliability, effectively resolving the inherent conflict between light-transmitting area and sealing strength.
[0038] 2. Through modular structural design and scalable manufacturing process, the present invention can flexibly expand the battery capacity from milliampere-hour to ampere-hour level, while maintaining excellent performance and adapting to large-scale production needs.
[0039] 3. The present invention designs the structure of light-rechargeable zinc ion soft-pack battery and optimizes the size of the optical window, which not only retains the good sealing of the battery, but also increases the capacity of the light-rechargeable zinc ion soft-pack battery and improves the utilization rate of light energy. The soft-pack battery prepared by the present invention has excellent comprehensive performance, 6.25cm 2Small soft pack battery at 1 A g -1 Achieve over 300 light-assisted cycle lifespans (capacity retention > 99%) at current density of 64cm 2 The size of the soft pack battery is 0.1A g -1 Under the light-assisted charging conditions of current density, a discharge capacity of 91.66 mAh can be demonstrated. The process of the present invention is simple and the cost is low, and it has good prospects and application space in the field of light energy storage batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a physical picture of a large-area photorechargeable zinc-ion soft-pack battery;
[0041] Figure 2 Schematic diagram of the decomposition of a large-area photorechargeable zinc-ion soft-pack battery;
[0042] In the figure, 1. Optical window; 2. ePTFE film; 3. Aluminum-plastic film; 4. Titanium mesh; 5. Photo cathode material; 6. GF / D glass fiber separator; 7. Zinc metal anode sheet;
[0043] Figure 3 is a schematic diagram of the bonding area;
[0044] In the figure, 3, aluminum-plastic film; 8, bonding area;
[0045] Figure 4 Schematic diagram of the hole array unit in the bonding area;
[0046] In the figure, the solid line represents each hole array unit, the dotted line represents each small square, each small square and the diagonal line of the hole array unit, and the dot represents the circular hole;
[0047] Figure 5 V6O 13 SEM images of nanosheets;
[0048] Figure 6 These are the charge and discharge curves of the large-area photorechargeable zinc ion soft-pack battery of Example 2 under light and dark conditions respectively;
[0049] Figure 7 These are the long cycle performance diagrams of the large-area photorechargeable zinc ion soft-pack battery of Example 2 under light and dark conditions respectively. DETAILED DESCRIPTION
[0050] The present invention is further described in detail below with reference to specific embodiments so that those skilled in the art can understand.
[0051] Example 1
[0052] V6O 13 Preparation
[0053] 1. Weigh 1.8-3 g of vanadium pentoxide (V2O5) and 2.7-4.5 g of oxalic acid dihydrate (H2C2O4·2H2O), and add 80 ml of deionized water.
[0054] Preferably, the mass of V2O5 is 2.4 g, and the mass of H2C2O4·2H2O is 3.6 g.
[0055] 2. Dissolve the weighed V2O5 and H2C2O4·2H2O in deionized water and heat with stirring at 60-90°C for 45-75 minutes. Transfer the solution to the inner lining of a 100ml reactor and install it into the reactor for a hydrothermal reaction at 160-200°C for 160-200 minutes.
[0056] Preferably, the heating and stirring temperature is 75° C., the heating and stirring time is 60 minutes, the hydrothermal reaction temperature is 180° C., and the hydrothermal reaction time is 180 minutes.
[0057] 3. After the hydrothermal reaction is completed, cool to room temperature, filter to obtain the precipitate, and wash and dry to obtain V6O 13 Nanosheets (vanadium oxide).
[0058] The prepared V6O 13 The nanosheets were subjected to SEM analysis, and the results were as follows Figure 5 As shown, the V6O prepared in this embodiment 13 The nanosheets have a uniform morphology.
[0059] Example 2
[0060] A large-area photorechargeable zinc-ion soft-pack battery
[0061] Combine Figure 1 and Figure 2 As shown, the preparation process of the large-area photorechargeable zinc ion soft-pack battery of this embodiment includes the following steps:
[0062] 1. Cut 4×8cm 2 The aluminum-plastic film was folded in half along the center of the 8 cm side, and a femtosecond laser system with a wavelength of 800 nm and a pulse width of 50 fs (repetition frequency of 1 kHz) was used to process a 1.5×1.5 cm 2 The optical window area (1.5×1.5cm 2 ) is the top surface area of the soft pack battery (4×4cm 2 ) of 14%.
[0063] 2. Define an area with a width of 0.2 cm around the optical window as the bonding area (such as Figure 3As shown in FIG), the femtosecond laser system in step 1 is used to process the hole array in the bonding area, as shown in FIG. Figure 4 As shown, each unit of the hole array is a square with a side length of 0.2 cm. Each hole array unit has four small squares of the same size. There are circular holes distributed at the center point of each small square and the center point of each hole array unit. The aperture of the circular holes is 1 μm.
[0064] 3. Cut 1.9×1.9cm 2 The aluminum-plastic film and ePTFE film treated in step 2 were cleaned for 300 seconds using a plasma cleaner with argon gas, a flow rate of 60 sccm, and a radio frequency of 240 W.
[0065] 4. Use acrylic adhesive to bond the ePTFE film to the bonding area of the aluminum-plastic film. The amount of acrylic adhesive used is 5~10μL / cm 2 The bonding width is 0.2 cm, and the acrylic adhesive is cured with an ultraviolet lamp. The power of the ultraviolet lamp is 6 watts and the curing time is 30 seconds to obtain an aluminum-plastic film bonded with an ePTFE film.
[0066] 5. Preparation of photorechargeable positive electrode sheet:
[0067] (1) Cut 2.5×2.5cm 2 30-mesh titanium mesh, leaving a 1×1 cm space in the upper right corner of the titanium mesh. 2 The large and small tabs were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain a clean and dry current collector titanium mesh.
[0068] (2) Weigh 70 mg of V6O prepared in Example 1 13 The nanosheets and 20 mg of acetylene black were placed in a mortar and ground thoroughly. 11 μl of PTFE emulsion was added and moistened with 1 mL of anhydrous ethanol. The mixture was stirred into a mass to obtain a photocathode material. The photocathode material was rolled onto the titanium mesh treated in step 1 using a roller press and dried in an oven at 60 ° C for 12 h to obtain a photorechargeable cathode sheet. The loading amount of the photocathode material was 8-15 mg / cm 2 .
[0069] 6. Preparation of electrolyte: Dissolve 0.03 mol of zinc trifluoromethanesulfonate in 10 ml of deionized water and stir at 500 r min under the action of a magnetic stirrer. -1 The mixture was stirred at a rate of 1 h to obtain a 3 mol / L zinc trifluoromethanesulfonate electrolyte.
[0070] 7. Cut 2.5×2.5cm 2 70μm thick zinc foil (high purity zinc foil) and leave a 1×1cm space in the upper left corner of the zinc foil2 The tabs of different sizes were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain the zinc metal negative electrode sheet. Cut into 3×3cm 2 GF / D glass fiber diaphragm.
[0071] 8. Combination Figure 2 As shown, from bottom to top, a zinc metal negative electrode sheet 7, a GF / D glass fiber separator 6, and a photorechargeable positive electrode sheet (with the side of the rolled photorechargeable positive electrode material 5 facing the GF / D glass fiber separator 6) are sequentially encapsulated within an aluminum-plastic film 3 bonded with an ePTFE film. The tabs of the photorechargeable positive electrode sheet and the tabs of the zinc metal negative electrode sheet are aligned, with the photorechargeable positive electrode sheet positioned near the optical window. After the zinc-ion battery is assembled, 700 μL of zinc trifluoromethanesulfonate electrolyte is added. A heat sealer is then used to seal the three edges, excluding the folded edge, twice. The heat seal is performed at a pressure of 0.4 MPa and a temperature of 180°C. The initial heat press is performed for 5 seconds, followed by a second heat press for 3 seconds after flipping the battery over. This results in a large-area photorechargeable zinc-ion soft-pack battery.
[0072] The adhesion strength between the aluminum-plastic film and the ePTFE film in the large-area light-rechargeable zinc ion soft-pack battery of this embodiment was measured. The peel strength test was performed using a 90° peeling method. The peel strength between the aluminum-plastic film and the ePTFE film in the large-area light-rechargeable zinc ion soft-pack battery of this embodiment was 326 gf / cm.
[0073] Comparative Example
[0074] Traditional zinc-ion soft-pack batteries
[0075] The preparation method of the zinc ion soft-pack battery in this comparative example is the same as that in Example 2, except that the hole array is not processed on the aluminum-plastic film, that is, step 2 in Example 2 is omitted.
[0076] The bonding strength between the aluminum-plastic film and the ePTFE film in the zinc ion soft-pack battery of the comparative example was measured, and the peel strength test was performed using the 90° peeling method. The peel strength between the aluminum-plastic film and the ePTFE film in the zinc ion soft-pack battery of this comparative example was 185 gf / cm, which was significantly lower than the peel strength in Example 2.
[0077] Example 3
[0078] Performance testing of large-area photorechargeable zinc-ion soft-pack batteries
[0079] 1. The large-area light-rechargeable zinc ion soft-pack battery prepared in Example 2 was tested for charge and discharge curves at a constant current density of 1000 mA / g in the dark and light, respectively. The test voltage range was 0.3-1.5 V. The results were as follows: Figure 6As shown in the figure, during the charging process, the battery's charge specific capacity increased from 267.2 mAh / g to 359.5 mAh / g, and the specific capacity increased by 34.54%. During the discharge process, the battery's discharge specific capacity increased from 268.5 mAh / g to 368.8 mAh / g, and the specific capacity increased by 37.35%. The light promotes the conversion of electrical energy into chemical energy, thereby greatly improving the battery capacity.
[0080] 2. The large-area light-rechargeable zinc ion soft-pack battery prepared in Example 2 and the conventional zinc ion soft-pack battery prepared in the comparative example were clamped with a transparent fixture such as an acrylic plate or a glass plate, and tested under light and dark conditions respectively. For the test under light conditions, the light intensity was 70 mW / cm 2 The light is irradiated vertically on the side of the aluminum plastic film containing the optical window. For the test under dark conditions, the battery is placed in a light-proof environment for testing. Figure 7 As shown in the figure, the cycle stability of the battery obtained by conventional packaging with conductive glass and hot melt adhesive is inferior to that of the large-area light-rechargeable zinc-ion soft-pack battery in Example 2. Under the conditions of the same positive electrode material, window area and electrolyte dosage, the battery with conventional packaging fails within 100 cycles due to electrolyte volatilization, while the large-area light-rechargeable zinc-ion soft-pack battery in Example 2 can stably cycle for more than 300 cycles.
[0081] Example 4
[0082] A large-area photorechargeable zinc-ion soft-pack battery
[0083] Combine Figure 1 and Figure 2 As shown, the preparation process of the large-area photorechargeable zinc ion soft-pack battery of this embodiment includes the following steps:
[0084] 1. Cut 5×11cm 2 The aluminum-plastic film was folded in half along the center of the 11 cm side, and a femtosecond laser system with a wavelength of 800 nm and a pulse width of 50 fs (repetition rate of 1 kHz) was used to process a 2.5×2.5 cm 2 The optical window area (2.5×2.5cm 2 ) is the top surface area of the soft pack battery (5×5.5cm 2 ) of 22.7%.
[0085] 2. Define an area with a width of 0.2 cm around the optical window as the bonding area (such as Figure 3 As shown in FIG), the femtosecond laser system in step 1 is used to process the hole array in the bonding area, as shown in FIG. Figure 4As shown, each unit of the hole array is a square with a side length of 0.2 cm. Each hole array unit has four small squares of the same size. There are circular holes distributed at the center point of each small square and the center point of each hole array unit. The aperture of the circular holes is 1 μm.
[0086] 3. Cut 2.9×2.9cm 2 The aluminum-plastic film and the ePTFE film treated in step 2 were cleaned for 300 seconds using a plasma cleaning machine with argon gas, a flow rate of 60 sccm, and a radio frequency of 240 W.
[0087] 4. Use acrylic adhesive to bond the ePTFE film to the bonding area of the aluminum-plastic film. The amount of acrylic adhesive used is 5~10μL / cm 2 The bonding width is 0.2 cm, and the acrylic adhesive is cured with an ultraviolet lamp. The power of the ultraviolet lamp is 6 watts and the curing time is 30 seconds to obtain an aluminum-plastic film bonded with an ePTFE film.
[0088] 5. Preparation of photorechargeable positive electrode sheet:
[0089] (1) Cut 4×4cm 2 30-mesh titanium mesh, leaving a 1×1 cm space in the upper right corner of the titanium mesh. 2 The large and small tabs were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain a clean and dry current collector titanium mesh.
[0090] (2) Weigh 140 mg of V6O prepared in Example 1 13 The nanosheets and 40 mg of acetylene black were placed in a mortar and ground thoroughly. Then, 22 μl of PTFE emulsion was added and moistened with 1.5 mL of anhydrous ethanol. After stirring into a mass, the photocathode material was obtained. The photocathode material was rolled onto the titanium mesh treated in step 1 using a roller press and dried in an oven at 60 ° C for 12 h to obtain a photorechargeable positive electrode sheet.
[0091] 6. Preparation of electrolyte: same as in Example 2.
[0092] 7. Cut 4×4cm 2 70μm thick zinc foil (high purity zinc foil), and leave 1×1cm 2 The tabs of different sizes were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain the zinc metal negative electrode sheet; cut into 4.5×4.5cm 2 Large and small GF / D fiberglass diaphragms.
[0093] 8. Combination Figure 2As shown, from bottom to top, a zinc metal negative electrode sheet 7, a GF / D glass fiber separator 6, and a photorechargeable positive electrode sheet (with the side of the rolled photorechargeable positive electrode material 5 facing the GF / D glass fiber separator 6) are sequentially encapsulated within an aluminum-plastic film 3 bonded with an ePTFE film. The tabs of the photorechargeable positive electrode sheet and the tabs of the zinc metal negative electrode sheet are aligned, with the photorechargeable positive electrode sheet positioned near the optical window. After the zinc-ion battery is assembled, 1600 μL of zinc trifluoromethanesulfonate electrolyte is added. A heat sealer is then used to seal the three edges, excluding the folded edge, twice. The heat seal is performed at a pressure of 0.4 MPa and a temperature of 180°C. The initial heat press is performed for 5 seconds, followed by a second heat press for 3 seconds after flipping the battery over. This results in a large-area photorechargeable zinc-ion soft-pack battery.
[0094] Example 5
[0095] A large-area photorechargeable zinc-ion soft-pack battery
[0096] Combine Figure 1 and Figure 2 As shown, the preparation process of the large-area photorechargeable zinc ion soft-pack battery of this embodiment includes the following steps:
[0097] 1. Cut 7×13cm 2 The aluminum-plastic film was folded in half along the center of the 13 cm side, and a femtosecond laser system with a wavelength of 800 nm and a pulse width of 50 fs (repetition frequency of 1 kHz) was used to process a 3×3 cm 2 The optical window area (3×3cm 2 ) is the top surface area of the soft pack battery (7×6.5cm 2 ) of 19.8%.
[0098] 2. Define a 0.4cm wide area around the optical window as the bonding area (e.g. Figure 3 As shown in FIG), the femtosecond laser system in step 1 is used to process the hole array in the bonding area, as shown in FIG. Figure 4 As shown, each unit of the hole array is a square with a side length of 0.4 cm. Each hole array unit has four small squares of the same size. There are circular holes distributed at the center point of each small square and the center point of each hole array unit. The aperture of the circular holes is 1 μm.
[0099] 3. Cut 3.8×3.8cm 2 The aluminum-plastic film and the ePTFE film treated in step 2 were cleaned for 300 seconds using a plasma cleaning machine with argon gas, a flow rate of 60 sccm, and a radio frequency of 240 W.
[0100] 4. Use acrylic adhesive to bond the ePTFE film to the bonding area of the aluminum-plastic film. The amount of acrylic adhesive used is 5~10μL / cm 2 The bonding width is 0.4 cm, and the acrylic adhesive is cured with an ultraviolet lamp. The power of the ultraviolet lamp is 6 watts and the curing time is 30 seconds to obtain an aluminum-plastic film bonded with an ePTFE film.
[0101] 5. Preparation of photorechargeable positive electrode sheet:
[0102] (1) Cut 5×5cm 2 30-mesh titanium mesh, leaving a 1×1 cm space in the upper right corner of the titanium mesh. 2 The large and small tabs were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain a clean and dry current collector titanium mesh.
[0103] (2) Weigh 210 mg of V6O prepared in Example 1 13 The nanosheets and 60 mg of acetylene black were placed in a mortar and ground thoroughly. 33 μl of PTFE emulsion was added and moistened with 2 mL of anhydrous ethanol. The mixture was stirred into a mass to obtain the photocathode material. The photocathode material was rolled onto the titanium mesh treated in step 1 using a roller press and dried in an oven at 60 °C for 12 h to obtain a photorechargeable positive electrode sheet.
[0104] 6. Preparation of electrolyte: same as in Example 2.
[0105] 7. Cut 5×5cm 2 70μm thick zinc foil (high purity zinc foil), and leave 1×1cm 2 The tabs of different sizes were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain the zinc metal negative electrode sheet; cut into 5.5×5.5cm 2 Large and small GF / D fiberglass diaphragms.
[0106] 8. Combination Figure 2 As shown, from bottom to top, a zinc metal negative electrode sheet 7, a GF / D glass fiber separator 6, and a photorechargeable positive electrode sheet (with the side of the rolled photorechargeable positive electrode material 5 facing the GF / D glass fiber separator 6) are sequentially encapsulated within an aluminum-plastic film 3 bonded with an ePTFE film. The tabs of the photorechargeable positive electrode sheet and the tabs of the zinc metal negative electrode sheet are aligned, with the photorechargeable positive electrode sheet positioned near the optical window. After the zinc-ion battery is assembled, 2500 μL of zinc trifluoromethanesulfonate electrolyte is added. A heat sealer is then used to seal the three edges, excluding the folded edge, twice. The heat seal is performed at a pressure of 0.4 MPa and a temperature of 180°C. The initial heat press is performed for 5 seconds, followed by a second heat press for 3 seconds after flipping the battery over. This results in a large-area photorechargeable zinc-ion soft-pack battery.
[0107] Example 7
[0108] A large-area photorechargeable zinc-ion soft-pack battery
[0109] Combine Figure 1 and Figure 2 As shown, the preparation process of the large-area photorechargeable zinc ion soft-pack battery of this embodiment includes the following steps:
[0110] 1. Cut 10×20cm 2 The aluminum-plastic film was folded in half along the center of the 20 cm side, and a femtosecond laser system with a wavelength of 800 nm and a pulse width of 50 fs (repetition frequency of 1 kHz) was used to process a 6×6 cm 2 The optical window area (6×6cm 2 ) is the top surface area of the soft pack battery (10×10cm 2 ) of 36%.
[0111] 2. Define an area with a width of 0.2 cm around the optical window as the bonding area (such as Figure 3 As shown in FIG), the femtosecond laser system in step 1 is used to process the hole array in the bonding area, as shown in FIG. Figure 4 As shown, each unit of the hole array is a square with a side length of 0.2 cm. Each hole array unit has four small squares of the same size. There are circular holes distributed at the center point of each small square and the center point of each hole array unit. The aperture of the circular holes is 1 μm.
[0112] 3. Cut to 6.4×6.4cm 2 The aluminum-plastic film and the ePTFE film treated in step 2 were cleaned for 300 seconds using a plasma cleaning machine with argon gas, a flow rate of 60 sccm, and a radio frequency of 240 W.
[0113] 4. Use acrylic adhesive to bond the ePTFE film to the bonding area of the aluminum-plastic film. The amount of acrylic adhesive used is 5~10μL / cm 2 The bonding width is 0.2 cm, and the acrylic adhesive is cured with an ultraviolet lamp. The power of the ultraviolet lamp is 6 watts and the curing time is 30 seconds to obtain an aluminum-plastic film bonded with an ePTFE film.
[0114] 5. Preparation of photorechargeable positive electrode sheet:
[0115] (1) Cut 8×8cm 2 30-mesh titanium mesh, leaving a 1×1 cm space in the upper right corner of the titanium mesh. 2 The large and small tabs were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain a clean and dry current collector titanium mesh.
[0116] (2) Weigh 560 mg of V6O prepared in Example 1 13 The nanosheets and 160 mg of acetylene black were placed in a mortar and ground thoroughly. 88 μl of PTFE emulsion was added and moistened with 4 mL of anhydrous ethanol. The mixture was stirred into a mass to obtain the photocathode material. The photocathode material was rolled onto the titanium mesh treated in step 1 using a roller press and dried in an oven at 60 °C for 12 h to obtain a photorechargeable positive electrode sheet.
[0117] 6. Preparation of electrolyte: same as in Example 2.
[0118] 7. Cut into 8×8cm 2 100μm thick zinc foil (high purity zinc foil), and leave 1×1cm 2 The tabs of different sizes were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain the zinc metal negative electrode sheet; cut into 8.5×8.5cm 2 Large and small GF / D fiberglass diaphragms.
[0119] 8. Combination Figure 2 As shown, from bottom to top, a zinc metal negative electrode sheet 7, a GF / D glass fiber separator 6, and a photorechargeable positive electrode sheet (with the side of the rolled photorechargeable positive electrode material 5 facing the GF / D glass fiber separator 6) are sequentially encapsulated within an aluminum-plastic film 3 bonded with an ePTFE film. The tabs of the photorechargeable positive electrode sheet and the tabs of the zinc metal negative electrode sheet are aligned, with the photorechargeable positive electrode sheet positioned near the optical window. After the zinc-ion battery is assembled, 6400 μL of zinc trifluoromethanesulfonate electrolyte is added. A heat sealer is then used to seal the three edges, excluding the folded edge, twice. The heat seal is performed at a pressure of 0.4 MPa and a temperature of 180°C. The initial heat press is performed for 5 seconds, followed by a second heat press for 3 seconds after flipping the battery over. This results in a large-area photorechargeable zinc-ion soft-pack battery.
[0120] Example 8
[0121] A large-area photorechargeable zinc-ion soft-pack battery
[0122] Combine Figure 1 and Figure 2 As shown, the preparation process of the large-area photorechargeable zinc ion soft-pack battery of this embodiment includes the following steps:
[0123] 1. Cut 4×8cm 2 The aluminum-plastic film was folded in half along the center of the 8 cm side, and a femtosecond laser system with a wavelength of 750 nm and a pulse width of 45 fs (repetition rate of 1.5 kHz) was used to process a 1.5×1.5 cm 2 The optical window area (1.5×1.5cm 2 ) is the top surface area of the soft pack battery (4×4cm2 ) of 14%.
[0124] 2. Define an area with a width of 0.8 cm around the optical window as the bonding area (such as Figure 3 As shown in FIG), the femtosecond laser system in step 1 is used to process the hole array in the bonding area, as shown in FIG. Figure 4 As shown, each unit of the hole array is a square with a side length of 0.8 cm. Each hole array unit has four small squares of the same size. There are circular holes distributed at the center point of each small square and the center point of each hole array unit. The aperture of the circular holes is 1 μm.
[0125] 3. Cut 3.1×3.1cm 2 The aluminum-plastic film and the ePTFE film treated in step 2 were cleaned for 360 seconds using a plasma cleaning machine with argon gas, a flow rate of 50 sccm, and a radio frequency frequency of 180 W.
[0126] 4. Use acrylic adhesive to bond the ePTFE film to the bonding area of the aluminum-plastic film. The amount of acrylic adhesive used is 5~10μL / cm 2 The bonding width is 0.8 cm, and the acrylic adhesive is cured with an ultraviolet lamp. The power of the ultraviolet lamp is 2 watts and the curing time is 40 seconds to obtain an aluminum-plastic film bonded with an ePTFE film.
[0127] 5. Preparation of photorechargeable positive electrode sheet:
[0128] (1) Cut 2.5×2.5cm 2 30-mesh titanium mesh, leaving a 1×1 cm space in the upper right corner of the titanium mesh. 2 The large and small tabs were ultrasonically cleaned with anhydrous ethanol for 25 minutes and then fully dried to obtain a clean and dry current collector titanium mesh.
[0129] (2) Weigh 50 mg of V6O prepared in Example 1 13 The nanosheets and 25 mg of acetylene black were placed in a mortar and ground thoroughly. Then, 25 μl of PTFE emulsion was added and moistened with 1.5 mL of anhydrous ethanol. After stirring into a mass, the photocathode material was obtained. The photocathode material was rolled onto the titanium mesh treated in step 1 using a roller press and dried in an oven at 60 ° C for 12 h to obtain a photorechargeable positive electrode sheet.
[0130] 6. Preparation of electrolyte: Dissolve 0.02 mol of zinc sulfate in 10 ml of deionized water and stir at 500 r min under the action of a magnetic stirrer. -1 The mixture was stirred at a rate of 1 h to obtain a 2 mol / L zinc sulfate electrolyte.
[0131] 7. Cut 2.5×2.5cm 230μm thick zinc foil (high purity zinc foil) and leave a 1×1cm space in the upper left corner of the zinc foil 2 The tabs of different sizes were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain the zinc metal negative electrode sheet. Cut into 3×3cm 2 GF / D glass fiber diaphragm.
[0132] 8. Combination Figure 2 As shown, from bottom to top, a zinc metal negative electrode sheet 7, a GF / D glass fiber separator 6, and a photorechargeable positive electrode sheet (with the side of the rolled photorechargeable positive electrode material 5 facing the GF / D glass fiber separator 6) are sequentially encapsulated within an aluminum-plastic film 3 bonded with an ePTFE film. The tabs of the photorechargeable positive electrode sheet and the tabs of the zinc metal negative electrode sheet are aligned, with the photorechargeable positive electrode sheet positioned near the optical window. After the zinc-ion battery is assembled, 700 μL of zinc sulfate electrolyte is added. A heat sealer is then used to seal the three edges, excluding the folded edge, twice. The heat seal is performed at a pressure of 0.2 MPa and a temperature of 110°C. The initial heat press is performed for 6 seconds, followed by a second heat press for 3 seconds after flipping the battery over. This results in a large-area photorechargeable zinc-ion soft-pack battery.
[0133] Example 9
[0134] A large-area photorechargeable zinc-ion soft-pack battery
[0135] Combine Figure 1 and Figure 2 As shown, the preparation process of the large-area photorechargeable zinc ion soft-pack battery of this embodiment includes the following steps:
[0136] 1. Cut 10×20cm 2 The aluminum-plastic film was folded in half along the center of the 20 cm side, and a femtosecond laser system with a wavelength of 850 nm and a pulse width of 55 fs (repetition rate of 0.5 kHz) was used to process an 8×8 cm 2 The optical window area (8×8cm 2 ) is the top surface area of the soft pack battery (10×10cm 2 ) of 64%.
[0137] 2. Define an area with a width of 0.2 cm around the optical window as the bonding area (such as Figure 3 As shown in FIG), the femtosecond laser system in step 1 is used to process the hole array in the bonding area, as shown in FIG. Figure 4 As shown, each unit of the hole array is a square with a side length of 0.2 cm. Each hole array unit has four small squares of the same size. There are circular holes distributed at the center point of each small square and the center point of each hole array unit. The aperture of the circular holes is 1.5 μm.
[0138] 3. Cut to 8.4×8.4cm 2 The aluminum-plastic film and the ePTFE film treated in step 2 were cleaned for 240 seconds using a plasma cleaning machine with argon gas, a flow rate of 70 sccm, and a radio frequency of 300 W.
[0139] 4. Use acrylic adhesive to bond the ePTFE film to the bonding area of the aluminum-plastic film. The amount of acrylic adhesive used is 5~10μL / cm 2 The bonding width is 0.2 cm, and the acrylic adhesive is cured with an ultraviolet lamp. The power of the ultraviolet lamp is 10 watts and the curing time is 10 seconds to obtain an aluminum-plastic film bonded with an ePTFE film.
[0140] 5. Preparation of photorechargeable positive electrode sheet:
[0141] (1) Cut 8.5×8.5cm 2 30-mesh titanium mesh, leaving a 1×1 cm space in the upper right corner of the titanium mesh. 2 The large and small tabs were ultrasonically cleaned with anhydrous ethanol for 25 minutes and then fully dried to obtain a clean and dry current collector titanium mesh.
[0142] (2) Weigh 640 mg of V6O prepared in Example 1 13 The nanosheets and 160 mg of acetylene black were placed in a mortar and ground thoroughly. Then, 160 μl of PTFE emulsion was added and moistened with 6 mL of anhydrous ethanol. After stirring into a mass, the photocathode material was obtained. The photocathode material was rolled onto the titanium mesh treated in step 1 using a roller press and dried in an oven at 60 °C for 12 h to obtain a photorechargeable positive electrode sheet.
[0143] 6. Preparation of electrolyte: Dissolve 0.008 mol of zinc chloride in 10 ml of deionized water and stir at 500 r min under the action of a magnetic stirrer. -1 The mixture was stirred at a rate of 1 h to obtain a 0.8 mol / L zinc chloride electrolyte.
[0144] 7. Cut to 8.5×8.5cm 2 200μm thick zinc foil (high purity zinc foil), and leave 1×1cm 2 The tabs of different sizes were ultrasonically cleaned with anhydrous ethanol for 30 minutes and then fully dried to obtain the zinc metal negative electrode sheet; cut into 9×9cm 2 Large and small GF / D fiberglass diaphragms.
[0145] 8. Combination Figure 2As shown, from bottom to top, a zinc metal negative electrode sheet 7, a GF / D glass fiber separator 6, and a photorechargeable positive electrode sheet (with the side of the rolled photorechargeable positive electrode material 5 facing the GF / D glass fiber separator 6) are sequentially encapsulated within an aluminum-plastic film 3 bonded with an ePTFE film. The tabs of the photorechargeable positive electrode sheet and the tabs of the zinc metal negative electrode sheet are aligned, with the photorechargeable positive electrode sheet positioned near the optical window. After the zinc-ion battery is assembled, 6400 μL of zinc chloride electrolyte is added. A heat sealer is then used to seal the three edges, excluding the folded edge, twice. The heat seal is performed at a pressure of 0.8 MPa and a temperature of 200°C. The initial heat press is performed for 3 seconds, followed by a second heat press for 1 second after flipping the battery over. This results in a large-area photorechargeable zinc-ion soft-pack battery.
[0146] Although the above embodiments have been described in detail, they are only a part of the embodiments of the present invention, not all of them. People can also obtain other embodiments based on this embodiment without inventiveness, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a large-area light-rechargeable zinc ion soft-pack battery, characterized in that: The following steps are involved: (1) Fold the aluminum-plastic film in half along the center of the edge, and use a femtosecond laser system to process an optical window in the center of one side of the aluminum-plastic film; (2) Define the bonding area around the optical window and use a femtosecond laser system to process the hole array in the bonding area; (3) Cleaning the aluminum-plastic film and expanded polytetrafluoroethylene film after processing in step (2); (4) bonding the expanded polytetrafluoroethylene film to the bonding area of the aluminum-plastic film using an acrylic adhesive, and performing UV curing to obtain an aluminum-plastic film bonded with the expanded polytetrafluoroethylene film; (5) Cleaning and drying the titanium mesh, rolling the photo-positive electrode material onto the titanium mesh, and obtaining a photo-rechargeable positive electrode sheet after drying; (6) From bottom to top, the zinc metal negative electrode sheet, GF / D glass fiber separator and photorechargeable positive electrode sheet are encapsulated in an aluminum-plastic film bonded with expanded polytetrafluoroethylene film. After the zinc ion battery is assembled, the electrolyte is added and the edges are hot-pressed to obtain a large-area photorechargeable zinc ion soft-pack battery.
2. The preparation method according to claim 1, wherein: In the step (1), the area of the optical window is 14-64% of the top surface area of the large-area light-rechargeable zinc ion soft-pack battery; The femtosecond laser system has a wavelength of 750-850 nm, a pulse width of 45-55 fs, and a repetition frequency of 0.5-1.5 kHz.
3. The preparation method according to claim 1, wherein: In step (2), the width of the bonding area is 0.2 to 0.8 cm; The hole array is composed of multiple hole array units, each of which is a square with a side length of 0.2 to 0.8 cm. Each hole array unit has four small squares of the same size. There are circular holes distributed at the center point of each small square and the center point of each hole array unit. The aperture of the circular holes is 1 to 1.5 μm.
4. The preparation method according to claim 1, wherein: In the step (3), the thickness of the expanded polytetrafluoroethylene film is 10-50 μm; The cleaning is performed using a plasma cleaning machine. The plasma of the plasma cleaning machine is argon gas with a flow rate of 50-70 sccm, a radio frequency power of 180-300 W, and a cleaning time of 240-360 seconds.
5. The preparation method according to claim 1, wherein: In step (4), the amount of acrylic adhesive used is 5~10μL / cm 2 The UV curing time is 10~40 seconds, and the UV curing power is 2~10 watts.
6. The preparation method according to claim 1, wherein: In the step (5), the cleaning is performed by ultrasonic cleaning with anhydrous ethanol for 25 to 30 minutes. The loading amount of the photo-positive electrode material on the photo-rechargeable positive electrode sheet is 8 to 15 mg / cm 2 ; The preparation steps of the photocathode material are as follows: V6O 13 The nanosheets and the conductive agent are mixed, ground, and then a binder is added. After wetting, the photocathode material is obtained by stirring.
7. The preparation method according to claim 6, characterized in that: The conductive agent is any one of acetylene black, Super P and carbon nanotubes, and the adhesive is any one of PTFE emulsion and PVDF emulsion; Conductive agent and V6O 13 The mass ratio of the nanosheets is 1:2~4, and the mass volume ratio of the conductive agent and the adhesive is 1:0.55~1mg / μl; V6O 13 The preparation steps of the nanosheets are as follows: Dissolve vanadium pentoxide and oxalic acid dihydrate in water, heat and stir, and then perform hydrothermal reaction. After the reaction is completed, cool and filter to obtain precipitate, wash and dry to obtain V6O 13 nanosheets; The mass ratio of vanadium pentoxide to oxalic acid dihydrate is 1.8-3:2.7-4.5, the heating and stirring temperature is 60-90° C., the heating and stirring time is 45-75 minutes, the hydrothermal reaction temperature is 160-200° C., and the hydrothermal reaction time is 160-200 minutes.
8. The preparation method according to claim 1, wherein: In the step (6), the zinc metal negative electrode sheet is obtained by ultrasonically cleaning and drying zinc foil, and the thickness of the zinc foil is 30-200 μm; The electrolyte is any one of zinc trifluoromethanesulfonate electrolyte, zinc sulfate electrolyte and zinc chloride electrolyte, and the concentration of the electrolyte is 0.8-3 mol / L; The hot pressing edge sealing is performed twice, the hot pressing temperature is 110-200° C., the hot pressing pressure is 0.2-0.8 MPa, the first hot pressing time is 3-6 seconds, and the large-area light-rechargeable zinc-ion soft-pack battery is turned over before the second hot pressing is performed, and the second hot pressing time is 1-3 seconds.
9. A large-area photorechargeable zinc ion soft-pack battery prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the large-area photorechargeable zinc ion soft-pack battery according to claim 9 in the field of energy storage.
Citation Information
Patent Citations
Photo-assisted rechargeable zinc ion battery and preparation method thereof
CN116130253A
Plastic -aluminum membrane structure for lithium cell
CN207594432U
Cited By
Preparation method of vanadium selenide vanadium oxide heterojunction photo-assisted zinc ion battery
CN122091799A